Bodmin Moor : an archaeological survey. - Johnson, Nicholas, 1950-; Rose, Peter, 1954-; Carter, Anne (English Heritage, 2013)
This is Volume 1 of the most extensive survey ever undertaken of the archaeological monuments of Bodmin Moor, a previously little-disturbed landscape.